PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN LIMBAH GERGAJIAN BATU ALAM DI DESA MADUREJO KECAMATAN PRAMBANAN KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Pranoto, Aji; ., Sudarsono (JURNAL GAUNG INFORMATIKA, 2016)
The purpose of the utilization of the waste of natural stone waste is 1) To increase  the capability and knowledge of the technique of utilization of solid waste stone waste   as well as powder professionally and efficiently, 2). Obtaining side income through  knowledge transfer of handicraf and mosaic manufacture, 3) Improving quality of life  by utilizing sawmill waste, 4) Increasing quality and added value of waste of stone  perngerga, 5) Reducing soil contamination due to solid and liquid waste on stone  sawing. 6) Creation of a clean, healthy and comfortable environment and free from  pollution due to sawn stone.Training procedures and practices of utilizing natural stone sawn waste as handycraf and mosaic have been implemented as planned and followed by 30 participants. The training was conducted at the home of one of the community service  team in collaboration with the totogan villagers and the pengarajin sawn stones.  Training begins with an explanation of the basic theories of materials, materials and  materials groups. Participants are taught by the direct practice of utilization of natural  stone sawdust waste both powder and solid. Participants were divided into 2 groups  consisting of 15 participants. Each group made mosaic of stone waste and made a  molding craft with powder, cement, hardener, cobalt and rezin. In this training is also  given how to create a mosaic that is true, strong and artistic and given training how to  make kerajian handycraf with a mixture of waste natural stone powder and cement used  as flower pots. while a mixture of powders, resins, hardener and cobal is molded by  making various handicrafts.   The results obtained that the participants have been able to create a natural stone mosaic with the size 30x30 cm and 40x40 cm and 5 cm thick. Mosaic of this natural stone can be used to be taped to the wall or home-garden home because it is more artistic. In the participants have been able to make miniature handycraf of prambanan temple, ashtray with picture of cat, horse, fish, and bird. At the end of the training each participant is distributed a team of mentoring funds for mosaic and handicraft molding materials as well as supporting materials such as cement and resin. As proof of their participation in training the utilization of natural stone participants are given a certificate. From the participants interest in participating in this training, it can be concluded that this epic skill training activity is very necessary for the citizens and the youth to drop out of school so that they will have additional skills and income which is useful for poverty alleviation.